Research on the timing of polymer flooding oil and water well fracturing - Zhang, Wei (E3S web of conferences, 2024)
Fracturing technology is the main measure to increase production and injection in oilfield production. With the gradual expansion of the scale of polymer flooding, the proportion of fractured Wells also increases year by year. How to maximize the benefits of fracturing measures has become the key technology, and the timing of fracturing is a major factor affecting the fracturing effect. By studying the fracturing time and effect of fracturing Wells in the industrial zone of polymer flooding, the optimal fracturing time of injection-production Wells is given. The fracturing time of injection Wells should be dominated by blank water drive stage and water-cut decline period. The producing Wells with low liquid production strength and low flow pressure are suitable for whole-well fracturing in water-cut decline period, and the thick-injection-thin production Wells dominated by river channels are suitable for fracturing in low-water cut period. Thin and differential Wells with differential production are suitable for fracturing during water-cut recovery period.